Dissecting the Quadruple Binary Hyad vA 351 Masses for Three M Dwarfs and a White Dwarf* - Benedict, G. Fritz; Franz, Otto G.; Horch, Elliott P.; Prato, L.; Torres, Guillermo; McArthur, Barbara E.; Wasserman, Lawrence H.; Latham, David W.; Stefanik, Robert P.; Latham, Christian; Skiff, Brian A. (The Astronomical Journal, 2021)
We extend results first announced by Franz et al., that identified vA 351 = H346 in the Hyades as a multiple star system containing a white dwarf. With Hubble Space Telescope Fine Guidance Sensor fringe tracking and scanning, and more recent speckle observations, all spanning 20.7 years, we establish a parallax, relative orbit, and mass fraction for two components, with a period, and total mass 2.1 . With ground-based radial velocities from the McDonald Observatory Otto Struve 2.1 m Telescope Sandiford Spectrograph, and Center for Astrophysics Digital Speedometers, spanning 37 years, we find that component B consists of BC, two M dwarf stars orbiting with a very short period ( days), having a mass ratio / = 0.95. We confirm that the total mass of the system can only be reconciled with the distance and component photometry by including a fainter, higher-mass component. The quadruple system consists of three M dwarfs (A, B, C) and one white dwarf (D). We determine individual M dwarf masses = 0.53 ± 0.10 , = 0.43 ± 0.04 , and = 0.41 ± 0.04 . The white dwarf mass, 0.54 ± 0.04 , comes from cooling models, an assumed Hyades age of 670 Myr, and consistency with all previous and derived astrometric, photometric, and radial velocity results. Velocities from Hα and He i emission lines confirm the BC period derived from absorption lines, with similar (He i) and higher (Hα) velocity amplitudes. We ascribe the larger Hα amplitude to emission from a region each component shadows from the other, depending on the line of sight.
Keywords: dept.phy; peer-reviewed

Zodiacal Exoplanets in Time (ZEIT). VII. A temperate candidate Super-Earth in the Hyades Cluster - Vanderburg, Andrew; Mann, Andrew W.; Rizzuto, Aaron; Bieryla, Allyson; Kraus, Adam L.; Berlind, Perry; Calkins, Michael L.; Curtis, Jason L.; Douglas, Stephanie T.; Esquerdo, Gilbert A.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2018)
Transiting exoplanets in young open clusters present opportunities to study how exoplanets evolve over their lifetimes. Recently, significant progress detecting transiting planets in young open clusters has been made with the K2 mission, but so far all of these transiting cluster planets orbit close to their host stars, so planet evolution can only be studied in a high-irradiation regime. Here, we report the discovery of a long-period planet candidate, called HD 283869 b, orbiting a member of the Hyades cluster. Using data from the K2 mission, we detected a single transit of a super-Earth-sized (1.96 0.12 R ⊕) planet candidate orbiting the K-dwarf HD 283869 with a period longer than 72 days. As we only detected a single-transit event, we cannot validate HD 283869 b with high confidence, but our analysis of the K2 images, archival data, and follow-up observations suggests that the source of the event is indeed a transiting planet. We estimated the candidate's orbital parameters and find that if real, it has a period P ≈ 100 days and receives approximately Earth-like incident flux, giving the candidate a 71% chance of falling within the circumstellar habitable zone. If confirmed, HD 283869 b would have the longest orbital period, lowest incident flux, and brightest host star of any known transiting planet in an open cluster, making it uniquely important to future studies of how stellar irradiation affects planetary evolution. © 2018. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: detection; stars: individual (HD 283869)